A book is just like you! : all about the parts of a book - Fox, Kathleen; Wallace, John, 1966- (Madison, Wisc. : Upstart Books, 2012)
Do you know that a book is just like you? It's true! Think about it: On the day you were born, you were given a name. A book is given a name, too -- it's called a title. You have a spine that helps to keep your body together. A book also has a spine, which keeps the book's body of pages together. You don't go to school naked -- you wear clothes to keep warm, protect your skin, show off your fashion sense and, of course, to keep out of the principal's office! Books wear clothes, too. A book's clothes are called a cover, or jacket, and like clothes, they keep the inside of a book protected from things like kids with sticky ice cream fingers and little baby brothers. With vibrant illustrations and hilarious comparisons, A Book is Just Like You is the perfect teaching tool for helping students understand their books -- inside and out.
Keywords: Books -- Juvenile literature; Publishers and publishing -- Juvenile literature